Environmental impact assessment of atmospheric emissions and water footprint in the 5 tourist transport companies at the Puno pier – 2025 (Aporte Santiaguino, 2025)
The study assessed the environmental impact of atmospheric emissions and water footprint generated by five tourist transport companies operating at the Puno pier during 2025. The objective was to identify the main sources of pollution and compare their operations based on fuel consumption, trip frequency, and water usage. The research employed a quantitative-descriptive methodology with a comparative component, using the TESTO 350 analyzer to measure CO, NOx, SO₂, and O₂, in addition to structured interviews with the managers of each company. The results showed that Amantaní and Soqta Suyo registered the highest emissions due to their longer routes, while the companies operating in Los Uros presented lower values ​​due to the shorter duration of their journeys. However, these companies accounted for more than 80% of total water consumption due to the frequent washing of their boats. Statistical analysis revealed significant differences between the companies, confirming the relationship between distance traveled, fuel consumption, and emissions generation. It is concluded that the sustainability of tourist transport in Puno requires integrated strategies for emissions reduction, optimization of water use and preventive maintenance, along with monitoring policies and environmental education to protect the ecosystem of Lake Titicaca.
Keywords: atmospheric emissions; tourist transport; water footprint